Prognostic Value of Preoperative Systemic Immune-Inflammation Index in Breast Cancer: A Propensity Score-Matching Study - Hua, Xin; Long, Zhi-Qing; Zhang, Yu-Ling; Wen, Wen; Guo, Ling; Xia, Wen; Zhang, Wen-Wen; Lin, Huan-Xin (Frontiers in Oncology, 2020)
Purpose: It was reported that the novel preoperative systemic immune-inflammation index (SII) can predict survival in cases of many malignant tumors. However, the prognostic significance of preoperative SII in breast cancer remains unclear. The purpose of this study was to investigate the relationship between SII and survival in breast cancer patients. Methods: Breast cancer patients (1026) who underwent a mastectomy at Sun Yat-sen University Cancer Center were retrospectively studied. The SII was determined using the following formula: neutrophil count × platelet count/lymphocyte count. The time-dependent receiver operating characteristic (ROC) curve was used to determine the optimal cut-off value for SII. Propensity score matching (PSM) was applied to develop comparable cohorts of high SII group and low SII group. Results: A total of 1026 patients were included as the primary cohort, and 894 patients were matched and regarded as the matched cohort. Patients were divided into two groups based on SII value: SII＜601.7 and high SII > 601.7. In the primary cohort, the 5-years overall survival (OS), recurrence-free survival (RFS), and distant metastasis-free survival (DMFS) rates for high SII group and low SII group were (85.6% vs. 91.3%, P = 0.016), (95.8% vs. 96.4%, P = 0.684) and (83.5% vs. 90.6%, P = 0.007), respectively. Univariate analysis showed that histological type, T stage, N stage, PR, HER2, Ki67 and SII all showed significant associations with OS; and histological type, T stage, N stage and SII all showed significant associations with DMFS. Multivariate survival analysis revealed that SII can independently predict OS (P = 0.017) and DMFS (P = 0.007). Similar results were found in PSM cohort. Conclusions: Preoperative SII may be a reliable predictor of OS and DMFS in patients with operable breast cancer to provide personalized prognostication and assist in formulation of the clinical treatment strategy.